Multicultural research as a backbone of teacher's formation: potential topics for the discussion about diversity and difference - Ivenicki, Ana (2008)
This paper argues that the comprehension of the research as a multicultural phenomenon can give the link teach-research a great significance to teachers formation. The article develops this idea by suggesting four main dimensions on this viewpoint: first, the conception of future teachers and teacher educators as researchers in action of plural cultural identity; second, the encouragement of discussions about educational themes in terms of silenced and represented voices, analyzing tensions between universal and diversity value; third, the expose of the future teachers to plural research methodologies; and finally, the analysis of the institution or organization identity where teachers formation happens, showing the problems related to unequal power relations and trying to make these institutions become multicultural organizations.